Discourse Tactic(s) in Police-Suspect Interactions in Ibadan, Nigeria. Issue 2 (4th May 2022) - Akinrinlola, Temidayo; Ajayi, Temitope
Abstract: Existing studies on police interrogation have revealed that investigating police officers (IPOs) often resort to the use of physical force in extracting confessional statements from suspects. However, we maintain that IPOs do not usually subject suspects to torture in a bid to obtain a confession. We therefore examine how IPOs use tactics to achieve confessions in police-suspect interactions (PSIs). Data comprise nine interactions between IPOs and suspects tape-recorded at the Criminal Investigation and Intelligence Department, Ìyágankú, Ibadan, Oyo State, Nigeria. Drawing on Bateson's framing theory, the study reveals that participants in PSIs resort to accentuation of crime, blaming of a third party, minimisation of crime, deployment of objections, use of alternative questions, avoidance of questions, oblique references, deliberate false statements, and resistance to achieve their respective goals. The study demonstrates that PSIs in Nigeria do not always involve the use of physical force by IPOs.